Gross morphological study of the brain of Sagor Sea Catfish, Hexanematichthys sagor (Actinopterygii: Siluriformes: Ariidae) - Nurul Fathiah Abdul Wahabi
The gross morphology of the brain of Hexanematichthys sagor and its relation with body allometry is described and discussed. The number of sample size is seventeen and all fishes were obtained from Pasar Utama Bintulu, Sarawak. The observation were made on the brain of Hexanematichthys sagor after the brain was extracted from the neuricranium and fixed in the 10% buffered formalin. There are nine morphometric characteristics that have been identified on the brain of Hexanematichthys sagor relative to the major subdivision. The cerebellum is the largest and more voluminous structure of the brain for this species. This condition is highly related with a high of motor coordination during swimming for most teleosts. The relative size of eminentia granularis, optic tectum, facial lobe and vagal lobe might associated with carnivorous feeding habit and the enhanced ability in food localization. The different pattern of allometry relationship between the brain and body is observed in this species. Simple linear regression analysis showed the negative allometry is observed for the whole length against body length while positive allometry is observed for the whole brain weight against body weight. The variation in the structure showed that the brains might be evolved for individual survival in its habitat. In conclusion, the Hexanematichthys sagor have a unique brain architecture that might reflect their ways of living.